Disruption of Cigarette Smoking Addiction After Dorsal Striatum Damage - Jing, Chuya; Jing, Changxin; Zheng, Liangcheng; Hong, Ganji; Zheng, Jingjing; Yu, Lu; Song, Ningning; Zhang, Tengkun; Ma, Qilin; Fang, Jie (Frontiers in Behavioral Neuroscience, 2021)
Studies have implicated a number of brain areas in addictive behavior, such as the insula, globus pallidus, amygdala, nucleus accumbens, and the midbrain dopamine system, but only a few studies have investigated the role of the dorsal striatum in addictive behavior. Our research found that patients who had a smoking addiction were more likely to have a disruption in their smoking addiction after they had dorsal striatum damage than those who had brain damage that did not involve the dorsal striatum. The disruption was characterized by the ability to quit smoking more easily and immediately, without relapse, and a reduced urge to smoke. These results suggest that the dorsal striatum is a critical neural substrate in addiction to smoking.